Seasonal influenza vaccination: Overcoming immunosenescence with enhanced vaccines - Wendy Boivin; Mark Loeb; Peter Openshaw; Mansoor Ashraf; Graham Pawelec (Vaccine: X)
Influenza causes substantial morbidity and mortality worldwide. Risks are increased in older adults aged 50–64 and ≥ 65 years. They are further exacerbated in those with age-related comorbidities. Immunosenescence (strictly defined here as detrimental age-related decline in the function of some or all parts of the immune system) is associated with increased susceptibility to influenza infection and more severe disease, a process that begins at approximately 50 years of age. Age-associated chronic low-level inflammation (inflammaging) may also increase influenza risk and is associated with more serious disease but may also enhance responses to high-dose vaccines in older adults. The frequency of comorbidities also increases with age. Frail older adults are at highest risk of influenza complications, but adults with high-risk comorbidities also show improved immune responses to enhanced influenza vaccines (high-dose, adjuvanted, recombinant). Moreover, clinical studies with some enhanced influenza vaccines show improved immunogenicity and greater efficacy or effectiveness, not only for persons aged ≥65 years but also in those aged 50–64 years. Reduced immunogenicity in persons aged 50–64 years may be even greater in those with comorbidities who would specifically benefit from receiving enhanced vaccines. Thus, accelerated immunosenescence, inflammaging, and chronic disease may place some adults aged 50–64 years at high risk of influenza, justifying meeting an unmet need in vaccination with enhanced vaccines normally used in persons ≥65 years of age.